Feasibility study on robot off-line programming and simulation using matlab tools : simmechanics and simulink packages - Hamzah, Ahmad (2004)
Since 19' . ABSTRACT h century, the development of robot in manufacturing industry have been increased rapidly, thus require the need to track down the historical development of robots by robot manufacturers that brings the robot function like todays. Due to demand, robot is said to be replacing human labour because of some factors such as its capability to do work effectively, reducing cost and task that human cannot do. In this research, a feasible study on robot off-line programming and simulation using MATLAB SimMechanics and Simulink packages will be the main objective. This project will be addressing about the development of robot modeling and simulation in the SimMechanics. It is aimed that this approach will be helping the academician and researchers in the related field because MATLAB is widely used in the world in various application.The result of this project shows that it is possible to do programming and 3D simulation using SimMechanics in order to obtain mechanical variables such as joint angle, angular acceleration, reaction force, and torque. SpaceLib program is then used to obtain the desired location and program each robot link to the respective coordinate system in matrix form